A Coal Mine Excavation Tunnels Modeling Method Based on Point Clouds - Haoyuan Zhang; Shanjun Mao; Mei Li (Applied Sciences)
The excavation tunnel model is an important reference for mine equipment control and tunnel deformation monitoring. Currently, tunnel models are mainly created manually, and point cloud reconstruction algorithms are difficult to directly apply to tunnel point clouds. To address these issues, this paper proposes a point cloud-based excavation tunnel modeling method. First, preprocessing algorithms such as point cloud coordinate transformation, tunnel point cloud extraction, and tunnel point cloud completion are used to filter out equipment point clouds inside the tunnel and repair occluded holes. Then, the tunnel centerline is extracted, and consistency optimization is performed on the point cloud normal vectors. Finally, a tunnel model is established based on the Poisson modeling algorithm, enabling high-precision tunnel modeling. The proposed algorithm’s accuracy and effectiveness are demonstrated through experiments on four different coal mine tunnels.